Examining the effects of race/ethnicity and other factors on outcomes of care for complex regional pain syndrome type 1 in the United States. - Anh Khoa Vo; James A G Crispo; Lisa J W Liu; Dylan Thibault; Allison W Willis; Donald E G Griesdale; John L K Kramer; Jacquelyn J Cragg (PLOS Global Public Health)
Complex regional pain syndrome is a chronic pain disorder marked by symptoms such as swelling, impaired motor function, and sympathetic dysfunction. Our primary objective was to determine the total number of complex regional pain syndrome type 1 (CRPS-1) emergency department (ED) visits and hospitalizations by race/ethnicity, as well as to assess sex and age distributions by race/ethnicity. Secondary objectives were to examine whether race/ethnicity, as well as select characteristics, are associated with hospitalization and longer length of stay. We completed a cross-sectional study of adults (19+ years) using acute and inpatient care data from the 2020 Nationwide Emergency Department Sample and the National Inpatient Sample. The overall rate of CRPS-1 diagnosis among ED visits and hospitalizations was 0.02% and 0.04%, respectively. Most CRPS-1 care was provided to White (ED: 83.1%; inpatient: 82.8%) patients. Within race/ethnicity groups, CRPS-1 ED visits and hospitalizations generally increased with age. Secondary findings included: 1) ED visits by Black individuals (compared with White) were significantly negatively associated with immediate hospitalization (adjusted odds ratio (AOR) 0.74, 95% CI 0.55 to 0.99); 2) hospitalizations by Black patients (compared with White) were independently associated with increased length of stay (odds ratio (OR) 1.45, 95% CI 1.07 to 1.96), though the association diminished with adjustment; and 3) drug abuse was significantly associated with hospitalization (AOR 4.67, 95% CI 3.53 to 6.18) and longer length of stay (AOR 1.81, 95% CI 1.34 to 2.46). Race/ethnicity was minimally associated with studied CRPS-1 outcomes. Additional studies are required to determine the impact of race/ethnicity on seeking care for CRPS-1.